A review of 65 years of human adenovirus seroprevalence - Franck J. D. Mennechet; Océane Paris; Aline Raissa Ouoba; Sofia Salazar Arenas; Sodiomon B. Sirima; Guy R. Takoudjou Dzomo; Amidou Diarra; Isidore T Traore; Dramane Kania; Karsten Eichholz; Eric A. Weaver; Edouard Tuaillon; et al. (Taylor & Francis Group, 2019)
Introduction: Human adenovirus (HAdV)-derived vectors have been used in numerous pre-clinical and clinical trials during the last 40 years. Current research in HAdV-based vaccines focuses on improving transgene immunogenicity and safety. Because pre-existing humoral immunity against HAdV types correlate with reduced vaccine efficacy and safety, many groups are exploring the development of HAdV types vectors with lower seroprevalence. However, global seroepidemiological data are incomplete. Areas covered: The goal of this review is to centralize 65 years of research on (primarily) HAdV epidemiology. After briefly addressing adenovirus biology, we chronical HAdV seroprevalence studies and highlight major milestones. Finally, we analyze data from about 50 studies with respect to HAdVs types that are currently used in the clinic, or are in the developmental pipeline. Expert opinion: Vaccination is among the most efficient tools to prevent infectious disease. HAdV-based vaccines have undeniable potential, but optimization is needed and antivector immunity remains a challenge if the same vectors are to be administrated to different populations. Here, we identify gaps in our knowledge and the need for updated worldwide epidemiological data.